Comparing Sexual Function and Quality of Life in Polycystic Ovary Syndrome and Healthy Women - Vida Shafti; Sara Shahbazi (Tehran University of Medical Sciences, 2016)
Objective: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders that is associated with different metabolic, reproductive and psychological consequences. The main aim of this study was to compare the sexual function and quality of life in women with polycystic ovary syndrome and healthy women. Materials and methods: This is a causal-comparative study in which 129 women with polycystic ovary syndrome were qualified as the research group. The control group consisted of 125 healthy women. The sampling method was convenient and was done using Rotterdam criteria. Women of both research and control groups responded to the FSFI and WHOQOL-BREF questionnaires. Data were analyzed with SPSS software using MANOVA. Results: According to findings, all of quality of life subscales except environment domain were significantly lower in research group than healthy group (p < 0.01), but none of sexual function subscales were significantly different between two groups (p > 0.05). Conclusion: Women with PCOS in term of some quality of life parameters have lower performance than healthy women. Therefore, it seems to be essential to increase awareness about symptoms and psychological consequences and referring process in order to take advantage of the advisory services.